Pengaruh Price Discount Dan Kualitas Produk Terhadap Keputusan Pembelian Online Pada Shopee Dengan Hedonic Shopping Motivation Sebagai Variabel Intervening (Studi Pada Mahasiswa FEB Universitas Islam Malang) - Iffah Alfi Masruroh; Abdul Kodir Djaelani; Arini Fitri Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine and analyze the effect of price discount and product quality on online purchasing decisions at Shopee with hedonic shopping motivation as an intervening variable for FEB students at the Islamic University of Malang. This type of research is using explanatory research with a quantitative approach. The sample in this study was 85 students of Management Faculty of Economics and Business, Islamic University of Malang class of 2018 as many as 85 people. Data was collected by distributing questionnaires. Analysis of the data used in this study using validity, reliability, normality, path analysis, multicollinearity, heteroscedasticity, t-test, coefficient of determination, and Sobel test. The results show that price discounts have a direct effect on hedonic shopping motivation, product quality has a direct effect on hedonic shopping motivation, price discounts have a direct effect on purchasing decisions, product quality has a direct effect on purchasing decisions, hedonic shopping motivation has a direct effect on purchasing decisions, hedonic shopping motivation can mediate price discounts on online purchasing decisions, and hedonic shopping motivation can also mediate product quality on online purchasing decisions. Keywords: Price Discount, Product Quality, Hedonic Shopping Motivation, Online Purchase Decision